The Effect of Capital Structure on Company Financial Performance - Nini Nini; Dina Patrisia; Agus Nurofik (Jurnal Economia, 2020)
Abstract: This study aims to examine the effect of capital structure on the company's financial performance particularly in manufacturing companies listed on the Indonesia Stock Exchange for the 4 years period from 2014 to 2018. Capital structure is measured by Market Total Leverage (MTLEV), Market Long-Term Leverage (MLLEV) and Market Short-Term Leverage (MSLEV). On the other hand, the company's financial performance is measured by Return on Equity (ROE) and Price to Book Value (PBV). The populations in this study are manufacturing companies listed on the Indonesia Stock Exchange and the selection of samples was determined by purposive sampling method, with the final samples as many as 333 company-years. The type of data used is secondary data from IDX using multiple regression analysis methods. The results of the analysis show that the capital structure has negative and significant effect on the company's financial performance in each model.Keywords: capital structure, company financial performance Pengaruh Struktur Modal Terhadap Kinerja Keuangan PerusahaanAbstrak: Penelitian ini bertujuan untuk menguji pengaruh struktur modal terhadap kinerja keuangan perusahaan pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2014-2018. Struktur modal diukur dengan Market Total Leverage (MTLEV), Market Long-Term Leverage (MLLEV) dan Market Short-Term Leverage (MSLEV). Sementara kinerja keuangan perusahaan diukur dengan Return on Equity (ROE) dan Price to Book Value (PBV). Populasi pada penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia. Sampel ditentukan dengan metode purposive sampling, kemudian sampel akhir diperoleh sebanyak 333 perusahaan-tahun. Jenis data yang digunakan adalah data sekunder dari IDX dengan menggunakan metode analisis regresi berganda. Hasil analisis menunjukan bahwa struktur modal berpengaruh negatif dan signifikan terhadap kinerja keuangan perusahaan disetiap model.Keywords: struktur modal, kinerja keuangan perusahaan